2014
DOI: 10.1590/s1516-8913201402331
|View full text |Cite
|
Sign up to set email alerts
|

Soybean β-Glucosidase immobilisated on chitosan beads and its application in soy drink increase the aglycones

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The results of IE of BGL (97%), after optimization, were higher than those observed for BGL immobilized in chitosan beads activated with 2.5% glutaraldehyde with IE of 73.8% (Grade et al, 2014). Immobilization of BGL in supports cellulose-rich materials was reporting at immobilization of Aspergillus niger BGL on spent coffee grounds obtain IE of 82% (Chen et al, 2013).…”
Section: Immobilization Of β-Glucosidase On Modified Sugarcane Bagassementioning
confidence: 76%
See 2 more Smart Citations
“…The results of IE of BGL (97%), after optimization, were higher than those observed for BGL immobilized in chitosan beads activated with 2.5% glutaraldehyde with IE of 73.8% (Grade et al, 2014). Immobilization of BGL in supports cellulose-rich materials was reporting at immobilization of Aspergillus niger BGL on spent coffee grounds obtain IE of 82% (Chen et al, 2013).…”
Section: Immobilization Of β-Glucosidase On Modified Sugarcane Bagassementioning
confidence: 76%
“…Thus, the addition SCB-immobilized enzyme in commercial soymilk increased the aglycone content, even though it was not in optimal conditions (pH 5.5), since the application was carried out in soymilk without changing its characteristics, including its pH being 7.2. Quitosan-immobilized soybean BGL applied in soymilk at optimal conditions of enzyme (pH 5.5 at 50 °C) increased by 24% in the aglycones contents after 60 min of incubation (Grade et al, 2014). The black soymilk added of spent coffee grounds or glass microspheres-immobilized Aspergillus niger BGL increased by 56% in the aglycones content, approximately, after 60 min or 120 min at optimal conditions of enzyme (pH 6 at 50 °C) (Chen et al, 2012(Chen et al, , 2013.…”
Section: Characterization Of Immobilized β-Glucosidasementioning
confidence: 92%
See 1 more Smart Citation
“…In recent years, many studies have emphasized on the enrichment of isoflavone aglycones in black soy milk by fermenting it with some probiotic microorganisms [ 12 14 ] or immobilized enzyme systems [ 15 18 ]. The bioconversion of isoflavone glucosides into aglycones was achieved through the removal of the glucoside conjugates using β -glucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…According to Park et al (2003) reported that β-glucosidase from Paenibacillus xylanilyticus KJ-03 was capable of hydrolyzing isoflavone daidzin and genistin. Moreover, the application of β-glucosidase and its immobilization could be an alternative choice to promote the bioconversion of the isoflavone glucosides to aglycones such as chitosan was used as stationary phase for immobilized β-glucosidase (Luciana et al, 2014). Lastly, isoflavone aglycones could be applied as bioactive food ingredients for healthy products or supplement food.…”
Section: Discussionmentioning
confidence: 99%